THE DISCONNECTED VOICES OF MOTHERHOOD AND DAUGHTERHOOD IN TONI MORRISON’S PARADISE: JOURNEY FROM UNCERTAINTY TO CHAOS - Ahdiyeh Alipour; Zanyar kareem Abdul (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
This paper is an attempt of analysing the problematic mother-daughter relationship in Paradise (1998), a female coming-of-age novel by Toni Morrison. In the novel, a black woman and her daughter had an uneasy relationship. The daughter strived to shape her own identity and future, but her uneasy relationship with her mother profoundly affected her choices and the way she lived. Undoubtedly, the patriarchal environment that had moulded the female identity and shaped a woman’s world resulted in a dysfunctional relationship between mother and daughter. Although the seed of maternal love existed in her heart as in all mothers, she was often incapable of transferring this love into words and actions, overwhelmed as she was by the pressures patriarchal society. The oppressive pressure on black women is depicted far surpassed that on the whites, and the former were ostracized from society merely because of who they were and by the colour of their skin. This paper explores how patriarchy and conventional beliefs could influence the mother-daughter relationship and prevented the expression of a mother’s true love, consequently depriving them of the opportunity or ability to perform physiologically and psychologically as mothers, biological or otherwise, in black communities. To liberate herself, the daughter had to struggle in the swamp, which her ancestors had created by the force of convention and patriarchy. However, when she eventually discovered the way to free herself from the swamp, she felt no welcome from society and so continued to remain isolated and ostracised.